CORRELATION OF PHYSICAL FUNCTIONAL CAPACITY AND SLEEP QUALITY IN THE ELDERLY AT GOTONG ROYONG HOSPITAL - Sugiyanto, Calista Sekar Langit Acintya; Wijono, Steven; Christy, Ari (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Introduction: Old age is a period that indicates a process of physical, mental, and social deterioration over time. There are several things that concern health in old age, one of which is functional status which is a major health problem in the elderly. A person's ability to perform daily activities can be assessed by their functional capacity. Physical functional capacity can be measured using the six-minute walk test (6MWT). There have been many studies that discuss the 6MWT, but none have specifically looked for the relationship between physical functional capacity and sleep quality in the elderly.Purpose: This study was conducted with the aim of knowing the relationship between physical functional capacity and sleep quality in the elderly at Gotong Royong Hospital.Methods: This study used an analytic observational research design with a cross sectional approach. Data were collected from demographic questionnaires, Pittsburgh Sleep Quality Index (PSQI), and direct 6MWT measurements. Data analysis in this study used univariate and bivariate analysis.Results: In this study, the results obtained p = 0.000 (p < 0.05) indicate that there is a significant relationship between physical functional capacity and the quality of sleep of the elderly at Gotong Royong Hospital.Conclusion: There is a relationship between physical functional capacity and elderly sleep quality at Gotong Royong Surabaya Hospital.